Bond Strength and Microleakage of a Novel Glass Ionomer Cement Containing Silver Diamine Fluoride - Auychai, Prim; Khumtrakoon, Nichakorn; Jitongart, Chonticha; Daomanee, Punnamas; Laiteerapong, Arunee (European Journal of Dentistry, 2021)
Objectives To investigate the shear bond strength and microleakage of glass ionomer cement (GIC) containing silver diamine fluoride (SDF).Materials and Methods Sound human permanent premolars were divided into the following three groups: 1) GIC (Fuji IX), 2) GICSDF-S: GIC + SDF (Saforide), and 3) GICSDF-T: GIC + SDF (Topamine). Shear bond strength (n = 14/group) was measured using a universal testing machine and compared between groups (one-way ANOVA and Tukey HSD, p < 0.05). Microleakage (n = 15/group) at enamel and dentin margins was scored using a stereomicroscope (10x) and compared between groups (Chi-square, p < 0.05).Results There were significant differences in shear bond strength between the GIC and GICSDF-S groups and between the GIC and GICSDF-T groups. The GIC group had the lowest shear bond strength among the groups; however, there was no significant difference between the GICSDF-S and GICSDF-T groups. The microleakage test results were not significantly different between groups at the enamel margin or dentin margins. Although the GIC group demonstrated a higher dye penetration score at the enamel and dentin margins, the difference was not significant.Conclusions Within the limitations of this study, we conclude that incorporating SDF into GIC results in higher shear bond strength while not increasing microleakage at the enamel and dentin margins.
Keywords: glass ionomer cement; microleakage; shear bond strength; silver diamine fluoride